Select the best: Positive selection to improve farm saved seed potatoes: Picture book - Gildemacher, P. (CTA / International Potato Center, 2009)
This manual provides a training approach for teaching farmers how to increase potato yields by improving the quality of farm-saved seed potatoes. After background information on seed potato degeneration, common potato diseases, selection issues and training methodology, it is divided into eight training modules, each one focused on a series of activities. It is accompanied by a Picture Book and a Farmer Field Aid (see 1541 and 1544).